Respuesta :
So here is how we are going to prove that (2(tan x - cot x) / (tan^2 x - cot^2 x} = sin (2x). Follow it step by step:
LS = 2(tanx−cotx)
------------------
tan^2−cot^2x
= 2(tanx−cotx)
----------------------
(tanx−cotx)(tanx+cotx)
= 2
-------------------
(tanx+cotx)
= 2
-----------------
Sin2x+cos2x
---------------- sinxcosx
= 2
-------------
1
------------
sinxcosx
= 2sinxcosx
= sin2x
I hope that is the answer that you are looking for. Let me know if you need more help next time. Thanks for posting your question here in brainly!
LS = 2(tanx−cotx)
------------------
tan^2−cot^2x
= 2(tanx−cotx)
----------------------
(tanx−cotx)(tanx+cotx)
= 2
-------------------
(tanx+cotx)
= 2
-----------------
Sin2x+cos2x
---------------- sinxcosx
= 2
-------------
1
------------
sinxcosx
= 2sinxcosx
= sin2x
I hope that is the answer that you are looking for. Let me know if you need more help next time. Thanks for posting your question here in brainly!
Answer:
tan(2x)=tan(x+x)
tan(x+x)
tan(x)+tan(x)/1-tan(x)tan(x)
2tan(x)/1-tan(x)^2
tan(2x)
tan(2x)=tan(x+x) is True.
tan(2x)=tan(x+x)
tan(x+x)
tan(x)+tan(x)/1-tan(x)tan(x)
2tan(x)/1-tan(x)^2
tan(2x)
tan(2x)=tan(x+x) is True.